Harnessing NK Cells for Cancer Treatment - Minetto, Paola; Guolo, Fabio; Pesce, Silvia; Greppi, Marco; Obino, Valentina; Ferretti, Elisa; Sivori, Simona; Genova, Carlo; Lemoli, Roberto Massimo; Marcenaro, Emanuela (Frontiers in Immunology, 2019)
In the last years Natural Killer (NK) cell-based immunotherapy has emerged as a promising therapeutic approach for solid tumors and hematological malignancies. NK cells are innate lymphocytes with an array of functional competences, including anti-cancer, anti‐viral and anti‐graft‐versus‐host disease potential. The intriguing idea of harnessing such potent innate immune system effectors for cancer treatment led to the development of clinical trials based on the adoptive therapy of NK cells or on the use of monoclonal antibodies targeting the main NK cell immune checkpoints. Indeed, checkpoint immunotherapy that targets inhibitory receptors of T cells, reversing their functional blocking, marked a breakthrough in anticancer therapy, opening new approaches for cancer immunotherapy and resulted in extensive research on immune checkpoints. However, the clinical efficacy of T cell-based immunotherapy presents a series of limitations, including the inhability of T cells to recognize and kill HLA-Ineg tumor cells. For these reasons, new strategies for cancer immunotherapy are now focusing on NK cells. Blockade with NK cell checkpoint inhibitors, that revers their functional block, may overcome the limitations of T cell-based immunotherapy, mainly against HLA-Ineg tumor targets. Here, we discuss recent anti-tumor approaches based on mAb-mediated blocking of immune checkpoints (either restricted to NK cells or shared with T cells), used either as single-agent or in combination with other compounds, that have demonstrated promising clinical responses in both solid tumors and hematological malignancies.